A redescription of the large geophilid centipede Chilenophilus corralinus (Attems, 1903) (Myriapoda: Chilopoda: Geophilomorpha), with new distribution records from southern Chile. (4th May 2017) - Pereira, Luis Alberto
ABSTRACT: The little known geophilomorph centipede Chilenophilus corralinus (Attems, 1903) (Myriapoda: Chilopoda, Geophilidae), a large geophilid species from South America is herein redescribed and illustrated based on new specimens collected in the Andes of Southern Chile. New morphological features of specific value are also given for the taxon. Chilenophilus corralinus is reported for the first time from the following Chilean localities: Region XIV (de Los Ríos region): Valdivia province: Pirihueico; camping "La Herradura"; Mafil. Region X (de Los Lagos region): Chiloé province: Chiloé Island. Llanquihue province: Parque Nacional Alerce Andino. Palena province: Hualaihué; Chaitén; Palena; Futaleufú.